Designing of Trifluoromethyl Substituted Pyrimidine Pharmacophore for Antiprostate Activity through a Collective Computational Approach - Asgaonkar, Kalyani; Tanksali, Sushruti; Abhang, Kshitija; Shevate, Krishna; Patil, Shital; Chitre, Trupti (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Prostate cancer is one of the leading causes of death. Though many drugs are being used as effective anticancer agents resistance and side effects necessitates development of target selective and safe anticancer agents. Objectives: The objectives of our work were to identify the important pharmacophoric features and correlate structure of Trifluoro substituted pyrimidine and predict their anticancer activity using QSAR, pharmacophore modelling, and docking studies. Materials and Methods: In this research investigation molecular modelling approach was adopted to develop efficacious Trifluoro substituted pyrimidine derivatives as anticancer agents. Results: Statistically significant models were generated using 2D-MLR method (correlation coefficient (r2) of 0.9207 and a significant Leave-one-out cross-validated correlation coefficient (q2) of 0.8187) and 3D QSAR studies by SA-kNN method (q2 = 0.723). 2D QSAR models indicated the important of SssNHcount and H- bond acceptor groups to augment the activity. Similarly, 3D QSAR results indicated the requirement of less electronegative and less steric substituents. Essential features such as aromatic and hydrogen bond acceptor features of compounds to interact with the target were highlighted using pharmacophore mapping. These studies prompted us to design new molecules using lead grow tool. Designed compounds were screened for their drug likeness, activity and toxicity using SWISS ADME, Osiris and PASS respectively. Finally docking and binding affinities of designed molecules were studied on EGFR 1M17. Conclusion: Thus, these studies collectively have helped to establish relationship between pyrimidine nucleus and anticancer activity.
Keywords: Prostate cancer; QSAR; Combilib; ADME; PASS; OSIRIS; Docking